The Gastronomic Traces of Bandung City: Preservation of European Culinary Heritage in Colonial and Post-Colonial Era - Tiffany Chairunnisa Ramadhania; Nova Maulidian Hidayat; Lien Maulina (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to analyze and mapping of European culinary heritage in Bandung by examining how historical narratives from the colonial-industrial, colonial-social, and post-colonial periods have been constructed, preserved, and reinterpreted to shape attraction and identities within Bandung’s gastronomic tourism landscape. Using a qualitative descriptive study approach , this research investigate three legendary culinary institutions: Bandoengsche Melk Centrale (BMC) 1928, Braga Permai, and Tizi Cake Shop & Restaurant. The finding identify three Culinary Heritage Preservation Models: the Adaptive-Hybrid Model, the Conservation Model, and the Authentic Specialization Model. Data were analyzed using the Dimensional Framework of Gastronomic Tourism Characteristics (Food as attraction, experience, heritage, and identity). The study concludes that Bandung’s gastronomic heritage continues to evolve through by historical trajectories and the creativity of local communities in reinforcing food as medium for perserving cultural identity and supporting the development of sustainable gastronomic tourism